ChemInform Abstract: New Perspectives in Organolanthanide Chemistry from Redox to Bond Metathesis: Insights from Theory. Issue 25 (June 2016) - Kefalidis, Christos E.; Castro, Ludovic; Perrin, Lionel; Rosal, Iker Del; Maron, Laurent
Abstract: Review: [a fifteen year contribution of computation studies in close synergy with experiments; 262 refs.